(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To analyze the correlation and similarity between transcutaneous PCO2 values (TcCO2) and PaCO2 in patients using high-flow oxygen during apnea during endoscopic vocal cord surgery. Research method: Randomized descriptive study on 45 patients undergoing endoscopic vocal cord surgery using high-flow oxygen during apnea at 108 Military Central Hospital from August 2023 to August 2024. Compare and analyze the correlation between TcCO2 and PaCO2 values in the above group of patients. Results: 45 patients were eligible to participate in the study with an average age of 40.50 ± 12.03 years. 315 pairs of arterial blood gas samples and TcCO2 values were recorded. TcCO2 and PaCO 2 values were well correlated (R2 = 0.94, p < 0.001), the mean difference was 1.69 mmHg and the range of similar limit values was from -2.97 to +6.35 mmHg (according to the Bland - Altman diagram). The difference between the indices PaCO2 and TcCO2 increased with the severity of PaCO2. Conclusion: There is a strong positive correlation between TcCO2 and PaCO2 values in patients using high-flow oxygen during respiratory arrest during endoscopic vocal cord surgery.